Investigation of interaction effect between static and rolling friction of corn kernels on repose formation by DEM - Shi, Linrong; Yang, Xiaoping; Zhao, Wuyun; Sun, Wei; Wang, Guanping; Sun, Bugong (International Journal of Agricultural and Biological Engineering, 2021)
The coefficient of static friction (SF), the coefficient of rolling friction (RF) for particles are two key parameters affecting the repose angle formation and flow characteristics. In this paper, the interaction effects of SF and RF on the formation process of corn repose angle was investigated by the discrete element method. Firstly, five shape kinds of corn models (horse tooth, spherical cone, spheroid, oblate, and irregular shape) were established. Secondly, aluminum cylinder and organic glass box were used to conduct the simulation experiments with taking SF and RF as independent factors and seeing the repose angle as dependent value. Based on simulation results the regression equations were established. Simulation results showed the relation between two factors and the rotational kinetic energy is not nonlinear, and SF does not significantly restrict the flow of corn models after increasing the flow direction, and the effect of SF on the contact number between corns and the bottom plate is remarkable, while the effect of RF on the contact number is not remarkable. Finally, the interaction effect of two factors on the repose angle was analyzed by variance analysis and results showed SF and RF all have a significant impact on the repose angle. Moreover, their interaction effect has an impact on the repose angle.Keywords: corn kernels, coefficient of static friction, coefficient of rolling friction, repose angle, interaction influenceDOI: 10.25165/j.ijabe.20211405.4357Citation: Shi L R, Yang X P, Zhao W Y, Sun W, Wang G P, Sun B G. Investigation of interaction effect between static and rolling friction of corn kernels on repose formation by DEM. Int J Agric & Biol Eng, 2021; 14(5): 238–246.